Hardcore data science. (O'Reilly Media, 2014)
"Welcome to the leading edge of data science, where new architectures and techniques for harnessing, analyzing, and exploring vast troves of information are being built and tested. In this O'Reilly video collection, you'll learn about recent advancements in data management, machine learning, natural language processing, crowdsourcing, and algorithm design from 11 data experts. Each video segment captures a presentation from the Hardcore Data Science track at the 2014 Strata Conference in Santa Clara, California."--Resource description page.